Signal Lost: Silence, Noise, and Digital Overload in Jennifer Egan’s The Candy House - Mary P, Salomia; K T , Dr Tamilmani (SMART MOVES JOURNAL IJELLH, 2025)
In a culture of relentless digital exposure where silence is scarce, connectivity constant, and attention fragmented, Jennifer Egan’s The Candy House (2022) stages a quiet rebellion. This paper examines how Egan transforms silence, noise, and technological saturation into both thematic material and narrative form to critique the erosion of human interiority in an algorithmic age. The novel’s speculative technology, “Own Your Unconscious,” dramatizes a collapse of signal—a world where meaning drowns in noise and selfhood fractures under overstimulation. Through a close reading of characters such as Bix Bouton, Lincoln, and Alfred Hollander, the study explores the psychological and affective costs of information excess. Drawing on posthuman theory, affect studies, and digital media ethics, it links Egan’s formal experimentation to her ethical critique of digital life. Moments of narrative pause and silence emerge not as voids but as acts of resistance gestures that reclaim agency within a culture addicted to exposure. The Candy House thus becomes a literary meditation on digital noise, affective exhaustion, and the fragile persistence of the self, asserting that in a world governed by incessant connectivity, silence endures as the last refuge of authenticity and ethical reflection.